Increased gut hormones and insulin sensitivity index following a 3-d intervention with a barley kernel-based product: a randomised cross-over study in healthy middle-aged subjects - Nilsson, Anne C.; Johansson-Boll, Elin V.; Björck, Inger M. E. (British journal of nutrition, 2015)
Certain purified indigestible carbohydrates such as inulin have been shown to stimulate gut-derived hormones involved in glycaemic regulation and appetite regulation, and to counteract systemic inflammation through a gut microbiota-mediated mechanism. Less is known about the properties of indigestible carbohydrates intrinsic to food. The aim of this study was to investigate the possibility to affect release of endogenous gut hormones and ameliorate appetite control and glycaemic control by ingestion of a whole-grain cereal food product rich in NSP and resistant starch in healthy humans. In all, twenty middle-aged subjects were provided with a barley kernel-based bread (BB) or a reference white wheat bread during 3 consecutive days, respectively, in a randomised cross-over design study. At a standardised breakfast the following day (day 4), blood was collected for the analysis of blood (b) glucose regulation, gastrointestinal hormones, markers of inflammation and markers of colonic fermentation; 3 d of intervention with BB increased gut hormones in plasma (p) the next morning at fasting (p-glucagon-like peptide-1; 56 %) and postprandially (p-glucagon-like peptide-2; 13 % and p-peptide YY; 18 %). Breath H2 excretion and fasting serum (s) SCFA concentrations were increased (363 and 18 %, respectively), and b-glucose (22 %) and s-insulin responses (17 %) were decreased after BB intervention. Insulin sensitivity index (ISIcomposite) was also improved (25 %) after BB. In conclusion, 3 d of intervention with BB increased systemic levels of gut hormones involved in appetite regulation, metabolic control and maintenance of gut barrier function, as well as improved markers of glucose homoeostasis in middle-aged subjects, altogether relevant for the prevention of obesity and the metabolic syndrome.